2021
DOI: 10.1093/pm/pnab122
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Dysmenorrhea Among University Students in Ireland

Abstract: Objective Primary dysmenorrhea (PD), or painful menstruation, is a common gynaecological condition that can cause intense pain and functional disability in women of reproductive age. As a non-malignant condition, PD is relatively under-studied and poorly managed. The purpose of this study was to estimate the prevalence and impact of PD among third-level students in Ireland. Design Cross-sectional observational study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
3
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 59 publications
6
34
3
7
Order By: Relevance
“…11,15,21,22 Lack of knowledge about the disease pathology, feeling of shyness, peer influence, and inadequate access to medical facilities are important factors. 24 Therefore, the students keep on tolerating the symptoms or try to self-manage their pain symptomatically without seeking medical advice. 16…”
Section: Discussionmentioning
confidence: 99%
“…11,15,21,22 Lack of knowledge about the disease pathology, feeling of shyness, peer influence, and inadequate access to medical facilities are important factors. 24 Therefore, the students keep on tolerating the symptoms or try to self-manage their pain symptomatically without seeking medical advice. 16…”
Section: Discussionmentioning
confidence: 99%
“…In addition, V (Water retention), VI (negative feelings) were higher before menstruation than after menstruation. Approximately two weeks before menstruation, a variety of physical and psychological symptoms emerge, which have the potential to negatively affect the quality of life (Durand et al, 2021). Health education for self-care behaviour is, therefore, needed as an intervention to maintain the quality of life due to the stress of menstruation-associated symptoms (Anikwe et al, 2020).…”
Section: Menstrual Discomfort Symptoms and Relevant Factorsmentioning
confidence: 99%
“…Dysmenorrhea can be classified as primary and secondary dysmenorrhea, with the former defined as pain occurring with menses in the absence of pelvic pathology, and the latter as menstrual pain associated with underlying pelvic pathology, such as endometriosis (Burnett and Lemyre, 2017). It is a common condition among women of reproductive age, and the severe pain experienced by dysmenorrhea sufferers often causes interference with daily and educational activities (Durand et al, 2021). A review of relevant literature published between 1944 and 2015 revealed that primary dysmenorrhea affects 45-95% of menstruating women worldwide (Iacovides et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A review of relevant literature published between 1944 and 2015 revealed that primary dysmenorrhea affects 45-95% of menstruating women worldwide (Iacovides et al, 2015). Other studies have shown prevalence rates of 74-94% in European countries (Abreu-Sánchez et al, 2020;Barcikowska et al, 2020;Durand et al, 2021), 72.1% among young Asian women (Abubakar et al, 2020), and 65.3% in Taiwan (Yeh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation